Redevelopment for urban poor: Assessing participatory strategies - Trivedi, Neeti; Tiwari, Reena (National Institute of Creative Arts and Industries, 2011)
Tensions are visible between spatial geography and the social order in contemporary city landscapes of both developing and developed countries. In Asian cities this ‘dual geography’ is visible where the rich seek protection within armed, gated communities with their shimmering high-rises away from or overlooking the organic, well-multiplied and established shanty settlements housing the urban poor. The vibrant informal sector within these shanty settlements constitutes 60 per cent of the city’s economy (Burdett & Rode, 2007), yet people living there remain marginalized. The question arises as to whether this vibrancy of the informal sector can be put to an improved use by the urban poor themselves. The purpose of this paper is to explore best practice in development strategies for urban poor. We examine a redevelopment project for urban poor in an Indian city. Here, a participatory approach has been used that searches for and identifies opportunities for socio-cultural, physical and economic wellbeing within the local context, offers alternate architectural technology using and interpreting local materials and skills, and involves the community from the planning to construction stages. This approach aids in local skills development and provides a sense of ownership towards the built environment. The key aspects of this approach are discussed in the context of wider literature on collaborative participation. They further provide a foundation for examining development strategies for urban poor in Australia. Although the contexts are totally different, with a view of re-development approaches in the developing and developed world, the paper attempts to find some common ground where synergies are visible for future improvement works, globally.